Effects of N-acetylcysteine on myocardial ischemia-reperfusion injury in bypass surgery - YALÇIN, AHMET SUHA; YÜKSEL, MERAL; AYKAÇ, ZEYNEP ZUHAL (SPRINGER, 2006)
Myocardial ischemia-reperfusion injury may complicate coronary artery bypass grafting (CABG) operations. N-Acertylcysteine (NAC) had antioxidant and microcirculatory effects, and inhibits neutrophil aggregation. The aim of this study was to determine the effects of NAC in limiting myocardial ischemia-reperfusion injury in CABG operations. Twenty patients undergoing elective coronary bypass operation with cardiopulmonary bypass were enrolled and randomly assigned to two groups: a control group operated with a routine CABG protocol, and one where NAC was administered intravenously during the operation (NAC group). Blood samples from coronary sinus for tumor necrosis factor-alpha assay, myocardial biopsy specimens for chemiluminescent luminol, and lucigenin measurements of reactive oxygen species were taken. The luminol (specific for .-OH, H2O2, and HOCl- radicals) and lucigenin (specific for O-2(.-)) levels and the difference ratios after reperfusion were significantly lower in the NAC group. Tumor necrosis factor-alpha levels increased in the control group but, in contrast, a significant decrease was detected in the NAC group (P < 0.01). Creatine kinase-MB levels at 6 and 12 hours were singnificantly lower in the NAC group (P = 0.02). N-Acetylcysteine has potential effects to limit ischemia reperfusion injury during CABG operations. We believe that its effects on clinical outcome may be more apparent in patients prone to ischemia-reperfusion injury.
Keywords: cardiovascular surgery; free radicals; N-acetylcysteine; tumor necrosis factor-alpha; reperfusion; endothelial function; REACTIVE OXYGEN; HEART; CHEMILUMINESCENCE; STRESS